Multicentre pragmatic embedded stepped wedge cluster randomised trial comparing glucose 5% with sodium chloride 0.9% as the default drug diluent in the ICU: the sweet-water trial protocol - Alexander Zarbock; Kai-Uwe Eckardt; Claudia Spies; Felix Balzer; Martin Witzenrath; Philipp Enghard; Björn Tampe; Oliver Hunsicker; Steffen Weber-Carstens; Bjoern Weiss; Jens Nee; Christian Strauss; et al. (BMJ Open)
Introduction Hypernatraemia, defined as a plasma sodium concentration >145 mmol/L, is a frequent complication in critically ill patients treated in the intensive care unit (ICU) (= ICU-acquired hypernatraemia), with reported prevalence ranging from 4% to 26%. Hypernatraemia adversely affects various physiological functions and is associated with delirium, prolonged length of stay and increased ICU and post-discharge mortality. The sodium load from intravenous drug diluents significantly contributes to ICU-acquired hypernatraemia, with drug infusions comprising about 30% of the daily fluid volume of an average ICU patient. This study aims to investigate if using glucose 5% solution as the default drug diluent, instead of sodium chloride 0.9%, can reduce the prevalence of ICU-acquired hypernatraemia and improve patient outcomes.Methods and analysis To test the effectiveness of glucose 5% solution as the default drug diluent, we will conduct a multicentre, pragmatic, embedded, open-label, stepped-wedge, cluster-randomised trial. The study will include twelve clusters (ICUs and one intermediate care unit) across six hospitals in Germany, with a projected total sample size of 4485 patients. In line with the stepped-wedge cluster-randomised design, one ICU will transition every 4 weeks, in a randomised sequence, from using sodium chloride 0.9% as the default drug diluent to glucose 5%.The primary endpoint is the prevalence of hypernatraemia >150 mmol/L through day 28. The number of days alive and free of the ICU through day 28 will be tested hierarchically as a key secondary endpoint. Other exploratory endpoints include ICU mortality, ICU-free days, hospital-free days and other clinical outcomes. The primary endpoint will be analysed using a logistic mixed-effects model.Ethics and dissemination The trial was approved by the Charité—Universitätsmedizin Berlin Ethics Board and by the ethics board of each enrolled hospital. The results will be submitted for publication in a peer-reviewed journal and presented at one or more scientific conferences.Trial registration number The trial protocol was registered with the German Clinical Trials Register on 21 June 2024 prior to initiation of patient enrolment (DRKS00033397).